Loneliness Mahasiswa selama pandemi COVID-19 - Asmita, Wenda -; Silvianetri, Silvianetri - (Jurnal Empati Bimbingan dan Konseling, 2023)
This study investigates student loneliness while studying at home/online during the pandemic. The research was conducted in the form of a literature study through accredited studies at Google Scholar. The main documents used are the last 2 years (2020) can be in English or Indonesian and are fully accessible. Based on the results of previous studies, it is known that students experience increased levels of loneliness during distance learning. Loneliness is defined as a condition in which students feel dissatisfied with their lives and are unable to develop warm and deep relationships with friends and the environment, leading to high levels of anxiety, depression and lack of social connections. Lonely people are often unhappy and dissatisfied with themselves and are reluctant to listen to others. It has even been found that some of the psychological disorders associated with loneliness, including emotional distress, self-harm, and degrade current mental health.